THE INFLUENCE OF TECHNOLOGY IN MODERN LIFE - Berdiqulova Mahbuba; To’raxonova Rayhonoy (TADQIQOTLAR, 2026)
ANNOTATION Technology plays a crucial role in shaping modern society and influencing everyday human activities. In the 21st century, rapid technological advancement has transformed communication, education, healthcare, and economic systems. This article provides an in-depth analysis of the role of technology in different spheres of life, highlighting both its advantages and disadvantages. It also discusses the challenges associated with digitalization, such as dependency, cybersecurity risks, and psychological effects. The findings suggest that while technology enhances efficiency and global connectivity, it must used responsibly to ensure sustainable development and human well-being.